2015
DOI: 10.1590/1806-9282.61.05.417
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of children and adolescents with lymphoblastic lymphoma

Abstract: OutcOme Of children and adOlescents with lymphOblastic lymphOma reV assoC med Bras 2015; 61(5):417-422 417

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The outcome was inferior for pleural or pericardial effusion positive patients comparing with negative ones in adolescent. And in a recent study by Burkhardt 11 , adolescent females with Pre-T-LBL had a worse outcome.…”
Section: Discussionmentioning
confidence: 91%
“…The outcome was inferior for pleural or pericardial effusion positive patients comparing with negative ones in adolescent. And in a recent study by Burkhardt 11 , adolescent females with Pre-T-LBL had a worse outcome.…”
Section: Discussionmentioning
confidence: 91%
“…13 Oliveira et al 14 reported a favourable prognosis of childhood LBL using an intensive chemotherapy regimen derived from acute lymphoblastic leukaemia therapy. Specifically, they reported that 22 (81%) of 27 patients were alive in first complete remission.…”
Section: Case Reportmentioning
confidence: 99%